2021
DOI: 10.3390/su132112137
|View full text |Cite
|
Sign up to set email alerts
|

Can Green Finance Development Reduce Carbon Emissions? Empirical Evidence from 30 Chinese Provinces

Abstract: Dealing with the relationship between environment and economic development is the core issue of China’s sustainable development. At present, China’s economic transformation is urgent, and green finance is being widely concerned. This paper measured the development level of China’s green finance from the perspective of green credit, green securities, green investment, and green insurance. Then, it used a spatial dynamic panel model to empirically test the mechanism of the impact of green finance on carbon emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(81 citation statements)
references
References 52 publications
3
75
0
3
Order By: Relevance
“…Chen et al (2021) empirically tested the influence mechanism of green finance on carbon emissions by using the spatial dynamic panel model. They believe that green finance contributes to carbon emission reduction, and the development of green finance indirectly leads to the reduction of carbon emissions by reducing financing constraints and promoting green technological innovation [ 41 ]. Jiang et al (2020) divided the research samples into high and low carbon emission groups according to the carbon emission intensity and studied the carbon reduction effects of green credit and green venture capital.…”
Section: Source and Analysis Of Datamentioning
confidence: 99%
“…Chen et al (2021) empirically tested the influence mechanism of green finance on carbon emissions by using the spatial dynamic panel model. They believe that green finance contributes to carbon emission reduction, and the development of green finance indirectly leads to the reduction of carbon emissions by reducing financing constraints and promoting green technological innovation [ 41 ]. Jiang et al (2020) divided the research samples into high and low carbon emission groups according to the carbon emission intensity and studied the carbon reduction effects of green credit and green venture capital.…”
Section: Source and Analysis Of Datamentioning
confidence: 99%
“…Compared with other innovation activities, green innovation is not only capital intensive, but also associated with high levels of risk, long cycles, and also requires long-term and stable financial support for enterprises to carry out green innovation activities [79]. Solving the problem of financial constraints is a key factor in promoting green innovation [80,81]. Regional happiness plays an important role in improving the efficiency of resource integration and promoting corporate green innovation, because high levels of local happiness play a positive role in enhancing interpersonal communication and social trust.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Based on the STIRPAT model, Shahbaz et al, analyzed the impact of Malaysia's urbanization rate, affluence, and trade openness on energy consumption, and found that the main factor affecting the growth of energy consumption is urbanization [18]. In addition, some scholars have analyzed the impact of foreign trade [19], environmental regulation [20], and financial development [21] on carbon emissions.…”
Section: Literature Reviewmentioning
confidence: 99%